Islamic Education Learning Model Based On The Cambridge Curriculum In Improving Quality Of Education - Yamin, Mochammad Ashabul; Astutik, Anita Puji (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Islamic education is the basis of Muslim civilization. The progress of Islamic education is closely related to the curriculum implemented in all educational units in Indonesia. Efforts to improve the quality of Islamic education must accommodate the needs of the times and adopt the latest developments in learning technology. In an effort to improve the quality of international standard education, the bilingual MTs Muslimat NU Pucang Sidoarjo adopted the Cambridge curriculum, which is integrated with the national curriculum and the Ministry of Religion, with the hope of being able to produce an Islamic generation that is civilized, critically reasoning, superior, and has an international outlook. Mastery of Arabic and English is important in integrating the curriculum. This research aims to analyze the implementation of the Cambridge curriculum at the bilingual MTs Muslimat NU Pucang Sidoarjo and the integration process with the existing curriculum. The approach used in this research is descriptive-qualitative, using field observation techniques and interviews with the principal, head of curriculum, and head of student affairs at MTs Bilingual Muslimat NU Pucang Sidoarjo. The research results show that the combination of the three curriculum is able to increase student activity, creativity, insight, and excellence.